NURSING STUDENTS` ATTITUDES TOWARDS MONITORING PATIENTS’ VITAL SIGNS - Pavlovic Jugovic, Katarina; Simin, Dragana (HEALTH CARE, 2023)
Introduction/aim: Data on the attitudes of nursing students towards the monitoring of patient’s vital signs are insufficient. The aim of this study was to examine the attitudes of students towards the monitoring of patients’ vital signs. Methods: The research was conducted as a cross-sectional study, by surveying 193 students of Undergraduate Academic Studies in Nursing and Undergraduate Applied Studies in Nursing at the Faculty of Medicine in Novi Sad. The data were collected using the general questionnaire and V-scale. Results: The attitude of the majority of nursing students (88.6%) regarding the monitoring of patient’s vital signs at the Faculty of Medicine in Novi Sad, according to the total score of the V-scale, was ambivalent. The largest number of students (91.7%) expressed a positive attitude towards the statements in the domain of communications, ambivalent in the domain of technologies (61.1%), and negative in the domain of key indicators (28.0%). The analysis of students’ attitudes towards vital signs monitoring in relation to gender showed a significant difference in the domain of communication. The value of the average score in the domain of communication was significantly lower in men (4.04+0.75) than in women (4.37+0.67). Students who had completed vocational secondary school had significantly higher values of average score in the domain of knowledge (3.44+0.72) in comparison to students who had previously completed high school or some other school (3.13+0.86), but a significant difference was not obtained for the other domains of V-scale. The students of final years in comparison to first-year students had significantly lower values of average scores in the domains of communication and knowledge. Conclusion: The obtained results of our study, in addition to the scientific one, also have professional significance, because pedagogical implications can be created based on them, as a basis for improving the existing content of clinical training in nursing studies.